Juvenile Xanthogranuloma - Lama, L.; Kayastha, B.M.M.K.; Tripathi, R. (Nepal Journal of Dermatology, Venereology & Leprology, 2016)
The histiocytoses are a heterogenous group of diseases that are characterized by the accumulation of reactive or neoplastic histiocytes in various tissues. Juvenile Xanthogranuloma is a member of the non-Langerhans cell group of histiocytic proliferative disorders. This present case report describes a juvenile xanthogranuloma in a twenty-month old male baby. Nepal Journal of Dermatology, Venereology & Leprology, Vol.14(1) 2016, pp.56-58